Virtual reality technologies for clinical education: evaluation metrics and comparative analysis - Mehrfard, Arian; Fotouhi, Javad; Taylor, Giacomo; Forster, Tess; Armand, Mehran; Navab, Nassir; Fuerst, Bernhard (Computer Methods in Biomechanics and Biomedical Engineering : Imaging & Visualization, 2021)
With recent advances of Virtual Reality (VR) technology, the deployment of such will dramatically increase in non-entertainment environments, such as professional education and training, manufacturing, service, or low frequency/high-risk scenarios. Clinical education is an area that especially stands to benefit from VR technology due to the complexity, high cost, and difficult logistics. The effectiveness of the deployment of VR systems in healthcare environments is subject to factors that may not be necessarily considered for devices targeting the entertainment market. In this work, we systematically compare a wide range of VR head-mounted displays (HMDs) technologies and designs by defining a new set of metrics that are 1) relevant to medical VR solutions and 2) are of paramount importance for VR-based education and training. We evaluated 10 technologies based on various criteria, including neck strain, heat development, cleanability, and colour accuracy. Other metrics such as text readability, comfort, and contrast perception were evaluated in a multi-user study on three selected technologies, namely the ones offered by Oculus Rift S, HTC Vive Pro and Samsung Odyssey+. Results indicate that the HTC Vive Pro performs best with regards to comfort, display quality and compatibility with glasses.
CRIS-Team Scopus Importer:2023-03-08
Keywords: head-mounted display; medical application; training; Virtual reality